2015
DOI: 10.1016/j.bmcl.2015.01.050
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecule with notable activity against multi-drug resistant tuberculosis

Abstract: Multi-drug resistant tuberculosis (MDR-TB) is emerging as a serious global health problem, which has been elevated through co-infection involving HIV and MDR-Mtb. The discovery of new compounds with anti-MDR TB efficacy and favorable metabolism profiles is an important scientific challenge. Using computational biology and ligand docking data, we have conceived a multifunctional molecule, 2, as a potential anti-MDR TB agent. This compound was produced through a multi-step synthesis. It exhibited significant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Streptomycin was used as a standard anti-MTB drug, but its MIC was not reported. The in vitro cytotoxicity of Compound 20 was evaluated in uninfected macrophages, and a relatively low percentage of macrophage viability inhibition was found (>85%) [101].…”
Section: Mtb Strainmentioning
confidence: 99%
“…Streptomycin was used as a standard anti-MTB drug, but its MIC was not reported. The in vitro cytotoxicity of Compound 20 was evaluated in uninfected macrophages, and a relatively low percentage of macrophage viability inhibition was found (>85%) [101].…”
Section: Mtb Strainmentioning
confidence: 99%
“…reported that compound 366 (earlier known to be a promising anti‐HIV integrase inhibitor) display impressive activity (MIC = 1.56 μg/mL) against MDR‐TB strain. Compound 366 also showed low cytotoxicity and possessed favorable metabolic profile against human cytochrome P450 and UGT isoenzyme, and when tested in combination with PA‐824, showed enhancement in activity (MIC = 0.195 μg/mL) . From the high‐throughput biochemical and NMR‐based fragment screening, Panda et al.…”
Section: Miscellaneous Structural Classesmentioning
confidence: 99%
“…Among these compounds, several heterocycles and scaffolds are contemplated, including benzo[ d ]isoxazole ( 39 ) [65], benzo[ b ]thiophenes ( 40 ) [66], disubstituted piperazine ( 41 ) [67], and benzoxazole ( 42 ) [68] (Figure 13). …”
Section: Antituberculosis Compoundsmentioning
confidence: 99%
“…Indeed, the scientific literature presents several works involving only the synthesis and phenotypic screening of compounds against MDR strains accompanied by in silico studies. Among these compounds, several heterocycles and scaffolds are contemplated, including benzo[ d ]isoxazole ( 39 ) [ 65 ], benzo[ b ]thiophenes ( 40 ) [ 66 ], disubstituted piperazine ( 41 ) [ 67 ], and benzoxazole ( 42 ) [ 68 ] ( Figure 13 ).…”
Section: Antituberculosis Compoundsmentioning
confidence: 99%
See 1 more Smart Citation